Experimental study of solar thermal energy storage finned tanks filled with different storage materials (PCM, gravel, and water) - Waleed Khalaf Jabbar; Ahmed Kadhim Alshara; Asiem Sahib Allawy (Results in Engineering)
Thermal energy storage systems are vital to overcome the mismatch between the solar energy harvesting and demand employing several sensible and latent heat storage materials. This work experimentally evaluates the thermal performance of thermal energy storage tanks filled with gravel, phase change material (PCM), and water. Each tank was provided with 29 circumferential fins, and blanketed with a thermal insulation to minimize heat losses. The average temperature variation during heat charging and discharging and the energy stored for each tank was discussed and evaluated to specify the best storage medium. Findings indicated that the PCM tank displayed the best performance, exhibiting lowest heat loss rates during energy discharging, with values of 6.184, 6.505, 5.998, 8.221, and 9.388 W during peak 5 h. Meanwhile, the water tank showed heat losses of 8.599, 8.866, 9.121, 9.400, and 9.295 while, the gravel tank disclosed 9.496, 9.535, 9.802, 12.364, and 9.914 W, indicating poorer thermal performance. Study outcomes revealed that the PCM tank stored higher thermal energy compared with the other tanks, reaching a maximum of 0.87 kWh. Besides, the water tank stored 0.37 kWh thermal energy due to its high thermal capacity, while the gravel tank stored as lowest energy as 0.1 kWh. Equivalently, the PCM tank has stored 135 % and 770 % more energy than the water and gravel tanks, respectively. In conclusion, the PCM tank maintained higher temperatures and energy storage for a longer duration than other tanks, demonstrating high potential of PCM as an effective energy storage option.